Pengalaman Perjumpaan Kebudayaan Jawa dan Flores Di Bagorejo Banyuwangi-Jawa Timur Dan Pentingnya Pendidikan Multikultural - Mathias Jebaru Adon (Anthropos: Jurnal Antropologi Sosial dan Budaya (Journal of Social and Cultural Anthropology), 2021)
The focus of this writing study aims to share a reflection of the experience of encounters between Javanese culture and Manggarai culture in Bagorejo Banyuwangi, East Java. The experience of this encounter reminds the author of the importance of multicultural education in Indonesia. As a pluralistic nation, encounters with other cultures cannot be avoided. On the one hand, the encounter enriches one another. However, on the other hand, the encounter caused a lot of conflict because of different perceptions and views. Based on this, it is very necessary to have a multicultural education system that starts from the elementary school level through learning and the introduction of other cultures. Through an education system like this, the authors found that to overcome attitudes of intolerance and radicalism that often occur in the country, an adequate multicultural understanding is needed. One of them is through multicultural learning which can be carried out with the Live-In program like the author did.